STUDENTS’ CULTURAL COMPETENCE THROUGH A CROSS-CULTURAL COMMUNICATION SUBJECT IN INDONESIA: A LITERATURE REVIEW - Andi Hamzah Fansury; Rampeng Rampeng (Publikasi dan UKI Press UKI Toraja., 2023)
Cross-Cultural Communication can be defined simply as a comprehensive way to examine similarities and differences between L1 culture and the target culture. It is a basic skill that the students need for developing an intellectual and emotional appreciation of cultures other than their own. Cross Cultural Communication can develop student’s cultural competencies as they experience lifelong learning. For specific cases, they can practice in stimulated exercises in order to develop their cultural competencies by bringing cultural exposure into the classroom for the specific purpose of teaching the target language culture. Since cultural competence enhancement is not static, the students’ interaction in multicultural life, their roles as English teacher candidates, and their life learning experiences will help them become more mature and will lead them to the level of cultural competence proficiency.